Amotekun: Assessing the Religious Paradox of a Community Policing Typology in South-Western States of Nigeria - Peter. O. O. Ottuh (Britain International for Academic Research (BIAR) Publisher, 2022)
The study assesses the religious paradox of Amotekun as a typology of community policing outfit in the South-Western States of Nigeria. Amotekun was created by the state governments out of a perceived failure of the Nigerian government to provide security and protection through the regular police force in the south-western states which are prone to serious insecurity challenges due to their populations’ outburst, economic realities and peculiar social environments. Second, the study addresses the dispute about the name and biblical (or religious) source for Amotekun which suggests a heightened religious sensitivity and debates leading to motivation for a viable area of intellectual research. The study is based on a critical historical review of extant literature, participant observation and personal interviews. The paper argues that it would not be easy to deny the irreligious and religiousness and Africanness of Amotekun as a typology of a community policing outfit.